Hungarian Monitoring, 16 September 1990 . [Magyar rádiófigyelő], 1990. szeptember 16 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - German unification - Soviet troops in Poland - Anti-government protests in Moscow Domestic Affairs: - József Antall in Rome - Göncz Árpád in Washington - Enrique W. Crespo visits Budapest - Arguments over the person of the foreign minister - Fighter plane crashes over Pápa Economy: - National Association of Entrepreneurs recommends economic amnesty Külpolitika: - Német egyesítés - Szovjet csapatok lengyelországi helyzete - Kormányellenes tüntetés Moszkvában Belpolitika: - Antall József Rómában - Göncz Árpád Washingtonban - Enrique W. Crespo Budapestre látogat - Viták a külügyminiszter személye körül - Lezuhant egy vadászgép Pápán Gazdaság: - Gazdasági amnesztiát javasol a VOSZ